Patterns of Partnership between Vocational Schools and Industry: Multi Case Study at VHS of Yosonegoro Magetan and State VHS 1 of Doko - Zustina Zustina; Yoto Yoto; Heru Wahyu Herwanto (Didaktika: Jurnal Kependidikan, 2024)
In the implementation of partnerships between SMK and industry so far, there are still problems such as the link and match between SMK and the industrial business world which has not yet led to the formation of a synergistic partnership. Therefore, this research aims to analyze the study of partnership patterns between SMK and PT Advantage SCM. This research method uses a qualitative approach with a multi-case study. The location of this research is at SMK Negeri 1 Doko and SMK Yosonegoro Magetan. The results showed that the planning of the partnership pattern between SMK and PT Advantage SCM was by conducting an MoU and synchronizing the curriculum. Then require teachers and students to take part in internships. Furthermore, the process of collaborating with the graduate distribution program by placing students in banks throughout Indonesia that work with PT Advantage. Supporting factors are adequate facilities and infrastructure and enthusiasm and motivation from the school and industry. The impact of the implementation of the partnership pattern is that students become more enthusiastic and confident, SMK saves on practical costs and is more trusted by the community, and industrial business world can reduce costs for recruitment.